Unveiling Equality: Exploring Gender Dynamics in India with Unbiased Perspective. - U Din Mir., Mehraj (International Journal of Psychosocial Rehabilitation, 2024)
Everyone is born without prejudice of any sort, such as ethnicity, sex, colour, language, birth, or any other status; they are equal in dignity and liberty, and everyone is entitled to all human rights and freedom. Women and men have received equal justice in ancient India and equal status in every sphere of life. This kind of treatment in present times has so far been an unrealised dream, which has tamed most of the individuals who are having high concerns for the equal status of women with great agony. A lip service is given by the power bearers by making tall promises to bring gender equality, which ends up in no results at the practical level. Hence the marginalisation of women, which consists nearly half of the population of Our country has had drastic results on them, as they have lagged behind men socio-politically and educationally. The paper tries to explore the contribution of our country’s political setup and the policy formulation in alienating women from opportunities that would have enabled them to contribute to society as men do. The paper also tries to explore the political consciousness of Indian women and the illusions created by the people who are at the helm of affairs. This paper also gives some highlights in order to bring gender egalitarianism to our country, for the development of any country is not feasible if it does not treat both the sexes equally. This paper would look into the drastic backdrops of "patriarchy" and how "feminism,” in retaliation, would help to build an egalitarian society.